2023
DOI: 10.1088/1674-1056/acd8b1
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating charge density wave state in kagome compound RbV3Sb5

Abstract: Owing to the unique electronic structure, kagome materials AV3Sb5 (A=K, Rb, Cs) provide a fertile platform of quantum phenomena such as the strongly correlated state and topological Dirac band. It is well known that RbV3Sb5 exhibits a 2×2 unconventional charge density wave (CDW) state at low temperature, and the mechanism is controversial. Here, by using scanning tunneling microscopy/spectroscopy (STM/STS), we successfully manipulated the CDW state in the Sb plane of RbV3Sb5, and realized a new √ 3×√ 3 modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…While these features are common to these metals with some degree of quantitative differences, distinctive features or material dependence have also been clearly observed. For example, scanning tunneling microscopy (STM) studies have reported a 4 × 1 charge order in CsV 3 Sb 5 4,8,22 and RbV 3 Sb 5 , 13,23,24 whereas it is not observed in KV 3 Sb 5 . 5,8,12 The CDW modulation pattern along the c -axis direction varies depending on the type of alkali metal.…”
Section: Introductionmentioning
confidence: 99%
“…While these features are common to these metals with some degree of quantitative differences, distinctive features or material dependence have also been clearly observed. For example, scanning tunneling microscopy (STM) studies have reported a 4 × 1 charge order in CsV 3 Sb 5 4,8,22 and RbV 3 Sb 5 , 13,23,24 whereas it is not observed in KV 3 Sb 5 . 5,8,12 The CDW modulation pattern along the c -axis direction varies depending on the type of alkali metal.…”
Section: Introductionmentioning
confidence: 99%